PERBEDAAN KEMAMPUAN MOTORIK KASAR SISWA KELAS 1 DAN KELAS 2 - kiki kiki Fatma; Y. Touvan Juni Samodra; Uray Uray Gustian; Rubiyatno Rubiyatno Rubiyatno; Ghana Firsta Yosika (STKIP Melawi, 2023)
This study aims to detrmine the differens in gross motor skills og grade 1 and grade 2 students in the coastel area at SD Negeri 27 Sungai Kakap throught motor tests such as Run, Gallop, Hoop, Horizontal jump, Leap, Slide, Catch, Striking stasionary ball, Kick, Overhead throw, Underhand rool, Stasionary dribble. The type of research conducted was descriptive quantitative which was conducted between researchers and elementary school children. The subjects studied were the children of 27 Sungai Kakap State Elmentary School, totaling 28 students. The results showed that class 2 motor skills were better than class 1 motor scores were 23.17 while grade 2 motor scores were 27.64. from the results of the study showed that class 2 is better than class 1 with a value of 27.64